2021
DOI: 10.1002/jrsm.1499
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced access to recommendations from the Cochrane Handbook for improving authors' judgments about risk of bias: A randomized controlled trial

Abstract: This randomized controlled trial (RCT) aimed to test the efficacy of enhanced access to Cochrane Handbook (Handbook) recommendations for judging the 2011 Cochrane risk of bias (RoB) domains for improving the adequacy of RoB judgments. Parallel‐group RCT with a 1:1 allocation ratio (N = 2271 per group) was conducted. Eligible participants were corresponding authors of all published Cochrane reviews and protocols. After allocation by a random number generator, participants received 20 scenarios for assessing RoB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…22 Our intervention achieved modest results, as the frequency of adequate RoB judgments was 7.1% higher in the intervention group (76.2%) than in the control group (69.0%). 22 However, even modest improvements on a large scale of systematic review production will achieve some effects. The enhanced access yields more adequate RoB assessments and could be incorporated into software supporting the RoB tool.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…22 Our intervention achieved modest results, as the frequency of adequate RoB judgments was 7.1% higher in the intervention group (76.2%) than in the control group (69.0%). 22 However, even modest improvements on a large scale of systematic review production will achieve some effects. The enhanced access yields more adequate RoB assessments and could be incorporated into software supporting the RoB tool.…”
Section: Discussionmentioning
confidence: 68%
“…The enhanced access yields more adequate RoB assessments and could be incorporated into software supporting the RoB tool. 22 Furthermore, this intervention can be combined with others to achieve better results.…”
Section: Discussionmentioning
confidence: 99%
“…Two investigators independently evaluated the quality of the literature using the Cochrane risk assessment tool (Barcot et al, 2021), which included six parts (selection bias, implementation bias, measurement bias, follow-up bias, reporting bias and other biases) with each aspect rated as low, high, or unclear in the risk of bias and then crosschecked the results. When there was any disagreement, they discussed the results with a third investigator to reach a consensus.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…Quality assessment of the RCTs was assessed based on the revised Cochrane risk-of-bias tool for randomized trials (RoB 2) (Sterne et al, 2019). In this tool, the study quality was have: 1) a low risk of bias, if a low risk of bias was observed in all domains; 2) a moderate risk of bias, if some concerns were present in at least one domain; or 3) a high risk of bias, if a high risk of bias was observed in at least one domain or some concerns were present for multiple domains such that the confidence in the result was substantially decreased (Sterne et al, 2019;Barcot et al, 2021).…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%